Juridical Review of Foreign Investment Opportunities in Reinsurance Business in Indonesia - Ihsan, Kamilul (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to conduct a juridical review of foreign investment opportunities in the reinsurance business in Indonesia. Reinsurance is a type of insurance that is carried out by insurance companies to protect themselves from risks of significant losses. Indonesia, as a developing country with a rapidly growing insurance industry, has great potential to attract foreign investment in the reinsurance industry. This study uses normative juridical research methods by analyzing laws and policies related to foreign investment in the reinsurance industry in Indonesia. The results show that although the opportunities for foreign investment in the reinsurance industry in Indonesia are significant, there are still several obstacles that need to be overcome, such as complex regulations and intense competition with domestic reinsurance companies. This study is expected to contribute to relevant stakeholders in developing the reinsurance industry in Indonesia through more effective and efficient foreign investment.